Pendekatan Sejarah (Historis) - Khoirul Bariah Rambe; Tiapisah Samosir (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The historical approach is a scientific method used to understand past events by examining elements such as time, place, actors, cause-and-effect relationships, and the broader socio-cultural context in which events occurred. In Islamic studies, this approach is especially important because religious teachings were revealed and practiced within particular historical situations. Understanding the historical background, including asbab al-nuzul, helps scholars interpret religious texts more accurately and avoid rigid or decontextualized interpretations. In addition, history has several functions, such as recreational, inspirational, instructive, and educational roles, which contribute to broadening insight, shaping moral character, and supporting effective learning processes. Historical research is conducted through systematic stages, including heuristics, verification, interpretation, and historiography, to ensure that historical analysis and writing are objective, credible, and accountable. Therefore, the historical approach serves as a fundamental framework in Islamic studies and other scientific fields for achieving a comprehensive, contextual, and sustainable understanding of the development of society, culture, and human thought.